Plasma membrane Ca2+ ATPase 1 (PMCA1) but not PMCA4 is critical for B‐cell development and Ca2+ homeostasis in mice. Issue 3 (16th November 2020) - Korthals, Mark; Tech, Laura; Langnaese, Kristina; Gottfried, Anna; Hradsky, Johannes; Thomas, Ulrich; Zenclussen, Ana Claudia; Brunner‐Weinzierl, Monika C.; Tedford, Kerry; Fischer, Klaus‐Dieter
Abstract: The amplitude and duration of Ca 2+ signaling is crucial for B‐cell development and self‐tolerance; however, the mechanisms for terminating Ca 2+ signals in B cells have not been determined. In lymphocytes, plasma membrane Ca 2+ ATPase (PMCA) isoforms 1 and 4 (PMCA1 and PMCA4, aka ATP2B1 and ATP2B4) are the main candidates for expelling Ca 2+ from the cell through the plasma membrane. We report here that Pmca4 ( Atp2b4 ) KO mice had normal B‐cell development, while mice with a conditional KO of Pmca1 ( Atp2b1 ) had greatly reduced numbers of B cells, particularly splenic follicular B cells, marginal zone B cells, and peritoneal B‐1a cells. Mouse and naïve human B cells showed only PMCA1 expression and no PMCA4 by western blot, in contrast to T cells, which did express PMCA4. Calcium handling was normal in Pmca4 −/− B cells, but Pmca1 KO B cells had elevated basal levels of Ca 2+, elevated levels in ER stores, and reduced Ca 2+ clearance. These findings show that the PMCA1 isoform alone is required to ensure normal B‐cell Ca 2+ signaling and development, which may have implications for therapeutic targeting of PMCAs and Ca 2+ in B cells. Abstract : PMCAs transport Ca 2+ from the inside to the outside of the cell. Although PMCA1 and PMCA4 are widely expressed, only PMCA1 is expressed on naïve B cells. PMCA1 is required for Ca 2+ extrusion and development of BM B cells, peritoneal B‐1a and B2 cells, and splenic follicular B cell and marginal zone B cell.